The Sensitivity and Specificity of Radiology and Histopathology in the Diagnosis of Posttraumatic Osteomyelitis - Braden, T. D.; Tvedten, H. W.; Mostosky, U. V.; Thomas, M.; Stickle, R. L.; Kaneene, J. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1989)
The sensitivity and specificity of radiology and histopathology in the diagnosis of post-traumatic osteomyelitis was determined. Post-traumatic osteomyelitis was created in one tibia of each of 31 dogs. Fifteen dogs did not receive treatment and sixteen dogs were treated with clindamycin (11 mg/kg body weight q 12 h, PO) for 28 days. At 8 wks post-inoculation week, S. aureus was isolated from nine of 31 dogs. Bacteriological reculture was the standard diagnostic test for osteomyelitis and was used as the standard for comparison in the calculations of the sensitivity and specificity of both radiology and histopathology. The sensitivity of radiology (radiological consensus of three radiologists) in the diagnosis of post-traumatic osteomyelitis at 8 weeks post-inoculation was 62.5% with a range among individual radiologists from 37.5% to 62.5%. The specificity of radiology (consensus) in the diagnosis of posttraumatic osteomyelitis at 8 weeks post-inoculation was 57.1% with a range among individual radiologists from 28.5% to 95.2%. The sensitivity of histopathology in the diagnosis of post-traumatic osteomyelitis at 8 weeks post-inoculation was 33.3%. The specificity of histopathology in the diagnosis of post-traumatic osteomyelitis at 8 weeks post-inoculation was 86.3%.
Keywords: Osteomyelitis; Diagnosis; Radiology; Histopathology; Sensitivity; Specificity